Moderating Roles of Resilience and Social Support on Psychiatric and Practice Outcomes in Nurses Working During the COVID-19 Pandemic - Anna E. Schierberl Scherr PhD; Brian J. Ayotte PhD; Marni B. Kellogg PhD, RN, CPN, CNE (SAGE Publishing, 2021)
Introduction Staff and equipment shortages and an easily transmissible virus make working in the COVID-19 pandemic demanding physically and psychologically. Nurses on the frontlines are particularly vulnerable to the adversity of working under these conditions, particularly with regard to mental health. Thus, understanding risk and protective factors for this vulnerable and essential group is critical for identifying potential targets of interventions. We had two aims for the current study: (a) to examine work functioning and symptoms of depression, anxiety, and posttraumatic stress (PTSD) among nurses who did and did not care for patients with COVID-19; and (b) to determine if resilience and social support moderate these relationships. Methods For three weeks in July 2020, nurses across the United States were invited to participate in an online survey collecting data on demographics, resilience, social support, and screening measures of depression, PTSD, anxiety, and distracted practice. Data were analyzed using descriptive statistics and hierarchical regression for each outcome measure. Conclusions Our findings support a growing body of research reporting that nurses are experiencing mental health sequelae during the COVID-19 pandemic, especially those providing direct care to patients with the virus. We found that compared to nurses who did not care for patients with COVID-19, those who did reported increased symptoms of PTSD, depression, and anxiety. A novel contribution is our finding that nurses providing direct COVID-19 care also experienced increased levels of distracted practice, a behavioral measure of distraction linking to a potential impact on patient care. We also found that resilience and social support acted as moderators of some of these relationships. Fostering resilience and social support may help buffer the effects of providing care to patients with COVID-19 and could potentially decrease nurse vulnerability to developing psychological symptoms and impairment on the job.